2004
DOI: 10.1023/b:joss.0000022379.95508.b2
|View full text |Cite
|
Sign up to set email alerts
|

Current Fluctuations in the One-Dimensional Symmetric Exclusion Process with Open Boundaries

Abstract: We calculate the first four cumulants of the integrated current of the one dimensional symmetric simple exclusion process of N sites with open boundary conditions. For large system size N , the generating function of the integrated current depends on the densities ρ a and ρ b of the two reservoirs and on the fugacity z, the parameter conjugated to the integrated current, through a single parameter. Based on our expressions for these first four cumulants, we make a conjecture which leads to a prediction for all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
209
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(224 citation statements)
references
References 40 publications
14
209
1
Order By: Relevance
“…Instead of trying to check an expression like (A.1) for the large deviation function we look for a symmetry at the level of its Legendre transform. As in [11], one knows that This is invariant under the symmetry λ → −2 log 2 − λ, implying that (A.2) is satisfied.…”
Section: Psfrag Replacementsmentioning
confidence: 96%
See 1 more Smart Citation
“…Instead of trying to check an expression like (A.1) for the large deviation function we look for a symmetry at the level of its Legendre transform. As in [11], one knows that This is invariant under the symmetry λ → −2 log 2 − λ, implying that (A.2) is satisfied.…”
Section: Psfrag Replacementsmentioning
confidence: 96%
“…The procedure to derive (3.11) is similar to what was done in [11]. One considers all the possible moves occurring during an infinitesimal time interval dτ and their contributions to exp λQ A (τ ) .…”
Section: Current Fluctuations On a General Graphmentioning
confidence: 99%
“…We begin with examining the simple lattice random walk case. We continue with an interacting lattice gas, namely the one dimensional exclusion process with periodic boundary conditions, for which our analytic results are somewhat less extensive, but that has in the recent past [11,12,8,29] served as a testbench for many of the ideas discussed in this introduction. In the case of the symmetric exclusion process we found that, though there is no first order dynamical phase transition, the event-counting observable mentioned above shows signs of a second order dynamical phase transition.…”
Section: Motivations and Outlinementioning
confidence: 99%
“…It is one of the few examples for which it has been possible to determine the distribution P (Q t ) both by microscopic and macroscopic approaches [4,5,8,13]. This distribution reveals that, for a long chain of length L connected at its two ends to two reservoirs at densities ρ a = 1 and ρ b = 0, the Fano factor (the ratio of the first two cumulants) is given, in the long time limit, by…”
mentioning
confidence: 99%